The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/antiox11020189
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of GIP against Monosodium Glutamate-Induced Ferroptosis in Mouse Hippocampal HT-22 Cells through the MAPK Signaling Pathway

Abstract: The effect of glucose-dependent insulinotropic polypeptide (GIP) on cells under oxidative stress induced by glutamate, a neurotransmitter, and the underlying molecular mechanisms were assessed in the present study. We found that in the pre-treatment of HT-22 cells with glutamate in a dose-dependent manner, intracellular ROS were excessively generated, and additional cell damage occurred in the form of lipid peroxidation. The neurotoxicity caused by excessive glutamate was found to be ferroptosis and not apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…In previous studies, glutamate activated autophagy in HT-22 cells [ 12 , 21 ], whereas CHOP expression had been shown to prevent autophagy [ 32 , 33 , 34 , 35 ] and ERK phosphorylation was regulated by autophagy proteins [ 36 ]; therefore, we investigated the effects of Rn-C and NpQ on autophagy induction in HT-22 cells subjected to 5 mM glutamate. LC3I conversion to LC3II is an indicator of autophagy induction, and thus, we measured the ratio of LC3II to LC3I via western blot ( Figure 8 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies, glutamate activated autophagy in HT-22 cells [ 12 , 21 ], whereas CHOP expression had been shown to prevent autophagy [ 32 , 33 , 34 , 35 ] and ERK phosphorylation was regulated by autophagy proteins [ 36 ]; therefore, we investigated the effects of Rn-C and NpQ on autophagy induction in HT-22 cells subjected to 5 mM glutamate. LC3I conversion to LC3II is an indicator of autophagy induction, and thus, we measured the ratio of LC3II to LC3I via western blot ( Figure 8 A).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, some others find them ineffective. Previous studies from this laboratory have reported caspase-12 cleavage, annexin V detection in glutamate treated HT-22 cells [ 21 ], and apoptosis-inducing factor (AIF) activation and caspase-independent cell death [ 43 ]. This all suggests that oxidative stress, caused by ER stress and mitochondrial leakage, induces a caspase-dependent or independent form of apoptosis; moreover, other conditions of cell death have been linked to glutamate toxicity in HT-22 cells, including the calpain, cathepsin, and the ubiquitin-proteasome system [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Zn 2+ -mediated neurodegeneration, protein kinase C (PKC)-induced Nox1 activation mediates transient receptor potential melastatin 2 (TRPM2)-dependent intercellular Ca 2+ overload via adenosine diphosphate ribose (ADPR) production, resulting in apoptosis [ 20 ]. A recent study also demonstrated that glutamate-induced ROS production, lipid peroxidation and hippocampal cell death is mediated by glucose-dependent insulinotropic polypeptide (GIP) and mitogen-activated protein kinase (MAPK)-induced Nox1 activation [ 21 ].…”
Section: Nox Proteins In Cns Signal Transductionmentioning
confidence: 99%